Measuring farm environmental sustainability in the Sierra del Rosario Biosphere Reserve - Gullotta, Gaia; Bergamini, Nadia; De Santis, Paola; Álvarez, Alejandro González; Martín, Jorge Luis Zamora; Menéndez, José Manuel Guzmán; Tormen, Nicola; Ruzzier, Enrico (Routledge, 2023)
This chapter presents an integrated methodology that combines a household survey with direct observations and measurements to understand the role and impact of farming activities within the Sierra del Rosario Biosphere Reserve and assess their sustainability and the relationship with the protected area. The methodology, based on an existing protocol (Biodiversity Friend), was adapted to Cuban traditional farming systems and further developed to include cultural, socio-economic, structural and natural variables. The methodology was applied in 24 farms with a large participation of farmers, resulting in an important knowledge sharing opportunity. Preliminary results show a high degree of naturality and sustainability in the highlands, particularly within the shade coffee plantations, a unique agroecosystem that combines high species richness and traditional varieties with traditional knowledge.